A Study on the Relation Between Absolute and Relative Size of the Team, and its Members’ Satisfaction - ديب كيندا; المقداد فايز; شاهين ماهر (Latakia University Journal - Economic and Legal Sciences Series, 2021)
There are a lot of studies that have relied on the results that the absolute size of a team is required for the performance of teams working on creative tasks. However, there is lack of research on the size of a team in relation to a team’s tasks and objectives (i.e., the relative size of a team). That is why, the present research aims at investigating the relation between the relative and absolute size of the teams working at the Scientific Agricultural Research Center in Lattakia and their members’ satisfaction. Lourenco et al. (2014) questionnaire was employed in this study to measure the satisfaction of team members. This questionnaire was distributed to 96 members who constitute 23 teams. These are the study sample that was chosen from the research population made up of the teams working in the center. It was found that there exists a significant correlation between the relative size of the team and the satisfaction of team members; and that there is no significant correlation between the absolute size of the team and the satisfaction of team members.